Exploring Intermediate Vocational Education and Training for 16-19 Year-olds in Germany and England - Higham, J. J. S.; Kremer, H.-Hugo; Yeomans, D. (The Architecture of Innovative Apprenticeship)

A story about a word: does narrative presentation promote learning of a spatial preposition in German two-year-olds? - Nachtigäller, Kerstin; Rohlfing, Katharina; McGregor, Karla K. (Journal of Child Language)
We trained forty German-speaking children aged 1;8–2;0 in their comprehension of UNTER [UNDER]. The target word was presented within semantically organized input in the form of a ‘narrative’ to the experimental group and within ‘unconnected speech’ to the control group. We tested children’s learning by asking them to perform an UNDER-relation before, immediately after, and again one day after the training using familiarized and unfamiliarized materials. Compared to controls, the experimental group learned better and retained more. Children with advanced expressive lexicons in particular were aided in generalizing to unfamiliarized materials by the narrative presentation. This study extends our understanding of how narrations scaﬀold young children’s enrichment of nascent word knowledge.

Biases in Management Forecasts of Venture-Backed Start-Ups: Evidence from Internal Due Diligence Documents of VC Investors - Sievers, Sönke; Mokwa, Christopher Frederik
This study provides evidence of significant biases in multi-year management forecasts by analyzing a proprietary dataset on venture-backed start-ups in Germany. We find that revenues and expenses are highly overestimated in each of the investigated one- to five-year-ahead planning periods. Furthermore, entrepreneurs underestimate one-year-ahead profit forecasts but clearly overestimate their profit forecasts for all longer-term forecast horizons. Additional analyses reveal that teams with prior management experience issue even more overestimated forecasts and misrepresent their forward-looking information. In contrast, greater asset verifiability and corporate lead investors are associated with lower levels of forecast errors. All key results hold if bias is either measured by traditionally comparing forecasts to ex-post realizations or by using a cross-sectional projection approach based on historical accounting data developed by prior research.
Keywords: Management forecasts; Forecasting biases; Venture-backed start-ups; Projection methods

The Relevance of Biases in Management Forecasts for Failure Prediction in Venture Capital Investments - Sievers, Sönke; Mokwa, Christopher Frederik
This study shows how venture capital investors can identify potential biases in multi-year management forecasts before an investment decision and derive significantly more accurate failure predictions. By advancing a cross-sectional projection method developed by prior research and using firm-specific information in financial statements and business plans, we derive benchmarks for management revenue forecasts. With these benchmarks, we estimate forecast errors as an a priori measure of biased expectations. Using this measure for our proprietary dataset on venture-backed start-ups in Germany, we find evidence of substantial upward forecast biases. We uncover that firms with large forecast errors fail significantly more often than do less biased entrepreneurs in years following the investment. Overall, our results highlight the implications of excessive optimism and overconfidence in entrepreneurial environments and emphasize the relevance of accounting information and business plans for venture capital investment decisions.
Keywords: Management forecast biases; cross-sectional projection models; venture-backed start-ups; failure prediction; overoptimism; overconfidence

Self-Organizing Particle Systems - Drees, Maximilian; Hüllmann (married name: Eikel), Martina; Koutsopoulos, Andreas; Scheideler, Christian (Proceedings of the 26th IEEE International Parallel and Distributed Processing Symposium (IPDPS))
Nanoparticles are getting more and more in the focus of the scientic community since the potential for the development of very small particles interacting with each other and completing medical and other tasks is getting bigger year by year. In this work we introduce a distributed local algorithm for arranging a set of nanoparticles on the discrete plane into specic geometric shapes, for instance a rectangle. The concept of a particle we use can be seen as a simple mobile robot with the following restrictions: it can only view the state of robots it is physically connected to, is anonymous, has only a constant size memory, can only move by using other particles as an anchor point on which it pulls itself alongside, and it operates in Look-Compute-Move cycles. The main result of this work is the presentation of a random distributed local algorithm which transforms any given connected set of particles into a particular geometric shape. As an example we provide a version of this algorithm for forming a rectangle with an arbitrary predened aspect ratio. To the best of our knowledge this is the rst work that considers arrangement problems for these types of robots.

The Relevance of Biases in Management Forecasts for Failure Prediction in Venture Capital Investments - Mokwa, Christopher Frederik; Sievers, Sönke (SSRN Electronic Journal)
This study shows how venture capital investors can identify potential biases in multi-year management forecasts before an investment decision and derive significantly more accurate failure predictions. By advancing a cross-sectional projection method developed by prior research and using firm-specific information in financial statements and business plans, we derive benchmarks for management revenue forecasts. With these benchmarks, we estimate forecast errors as an a priori measure of biased expectations. Using this measure for our proprietary dataset on venture-backed start-ups in Germany, we find evidence of substantial upward forecast biases. We uncover that firms with large forecast errors fail significantly more often than do less biased entrepreneurs in years following the investment. Overall, our results highlight the implications of excessive optimism and overconfidence in entrepreneurial environments and emphasize the relevance of accounting information and business plans for venture capital investment decisions.
Keywords: Management forecast biases; cross-sectional projection models; venture-backed start-ups; failure prediction; overoptimism; overconfidence

Biases in Management Forecasts of Venture-Backed Start-Ups: Evidence from Internal Due Diligence Documents of VC Investors - Mokwa, Christopher; Sievers, Sönke (SSRN Electronic Journal)
This study provides evidence of significant biases in multi-year management forecasts by analyzing a proprietary dataset on venture-backed start-ups in Germany. We find that revenues and expenses are highly overestimated in each of the investigated one- to five-year-ahead planning periods. Furthermore, entrepreneurs underestimate one-year-ahead profit forecasts but clearly overestimate their profit forecasts for all longer-term forecast horizons. Additional analyses reveal that teams with prior management experience issue even more overestimated forecasts and misrepresent their forward-looking information. In contrast, greater asset verifiability and corporate lead investors are associated with lower levels of forecast errors. All key results hold if bias is either measured by traditionally comparing forecasts to ex-post realizations or by using a cross-sectional projection approach based on historical accounting data developed by prior research.
Keywords: Management forecasts; Forecasting biases; Venture-backed start-ups; Projection methods

Regional and socio-economic differences in food, nutrient and supplement intake in school-age children in Germany: results from the GINIplus and the LISAplus studies - Sausenthaler, Stefanie; Standl, Marie; Buyken, Anette; Rzehak, Peter; Koletzko, Sibylle; Bauer, Carl Peter; Schaaf, Beate; von Berg, Andrea; Berdel, Dietrich; Borte, Michael; Herbarth, Olf; Lehmann, Irina; et al. (Public Health Nutrition)
Abstract Objective To describe regional differences between eastern and western Germany with regard to food, nutrient and supplement intake in 9–12-year-old children, and analyse its association with parental education and equivalent income. Design Data were obtained from the 10-year follow-up of the two prospective birth cohort studies – GINIplus and LISAplus. Data on food consumption and supplement intake were collected using an FFQ, which had been designed for the specific study population. Information on parental educational level and equivalent income was derived from questionnaires. Logistic regression modelling was used to analyse the effect of parental education, equivalent income and region on food intake, after adjusting for potential confounders. Setting Germany. Subjects A total of 3435 children aged 9–12 years. Results Substantial regional differences in food intake were observed between eastern and western Germany. Intakes of bread, butter, eggs, pasta, vegetables/salad and fruit showed a significant direct relationship with the level of parental education after adjusting for potential confounders, whereas intakes of margarine, meat products, pizza, desserts and soft drinks were inversely associated with parental education. Equivalent income had a weaker influence on the child's food intake. Conclusions Nutritional education programmes for school-age children should therefore account for regional differences and parental education.

Buy, Sell, or Hold? Information Extraction from Stock Analyst Reports - Lee, Yeong Su; Geierhos, Michaela (Modeling and Using Context: 7th International and Interdisciplinary Conference, CONTEXT 2011, Karlsruhe, Germany, September 26-30, 2011, Proceedings)
This paper presents a novel linguistic information extraction approach exploiting analysts’ stock ratings for statistical decision making. Over a period of one year, we gathered German stock analyst reports in order to determine market trends. Our goal is to provide business statistics over time to illustrate market trends for a user-selected company. We therefore recognize named entities within the very short stock analyst reports such as organization names (e.g. BASF, BMW, Ericsson), analyst houses (e.g. Gartner, Citigroup, Goldman Sachs), ratings (e.g. buy, sell, hold, underperform, recommended list) and price estimations by using lexicalized finite-state graphs, so-called local grammars. Then, company names and their acronyms respectively have to be cross-checked against data the analysts provide. Finally, all extracted values are compared and presented into charts with different views depending on the evaluation criteria (e.g. by time line). Thanks to this approach it will be easier and even more comfortable in the future to pay attention to analysts’ buy/sell signals without reading all their reports.

Sound & Image. An experimental study on the influence of acoustical parameters on the perception of a product’s image in TV-commercials - Flath, Beate (Audio Branding Year Book 2010)